El buen gobierno corporativo en las sociedades cooperativas - Puentes Poyatos, Raquel; Velasco Gámez, María Del Mar; Vilar Hernández, Juan (REVESCO. Revista de Estudios Cooperativos, 2009)
In recent years corporate governance has become in a key indicator of good management, being published a multitude of codes of good governance in order to strengthen management systems, control and management of enterprises, making them more transparent, efficient and democratic. In this regard, three Codes of corporate governance have been published at the moment in Spain: the Olivencia Code in 1998, which was followed by the Aldama Code in 2003 and the Unified Code of good governance in 2006. This article aims to analyze whether the Unified Code, as code or guide to good corporate practices, will apply to all types of companies, or otherwise is lacking for the use of cooperative societies that invites to develop their own code for this social type or the adaptation of the one that exists.